Intrinsically High Capacity of Animal Cells From a Symbiotic Cnidarian to Deal With Pro-Oxidative Conditions - Cotinat, Pauline; Fricano, Clara; Toullec, Gaëlle; Röttinger, Eric; Barnay-Verdier, Stéphanie; Furla, Paola (Frontiers in Physiology, 2022)
The cnidarian-dinoflagellate symbiosis is a mutualistic intracellular association based on the photosynthetic activity of the endosymbiont. This relationship involves significant constraints and requires co-evolution processes, such as an extensive capacity of the holobiont to counteract pro-oxidative conditions induced by hyperoxia generated during photosynthesis. In this study we analyzed the capacity of Anemonia viridis cells to deal with pro-oxidative conditions by in vivo and in vitro approaches. Whole specimens and animal primary cell cultures were submitted to 200 and 500 μM of H2O2 during 7 days. Then, we monitored global health parameters (symbiotic state, viability and cell growth) and stress biomarkers (global antioxidant capacity, oxidative protein damages and protein ubiquitination). In animal primary cell cultures, the intracellular ROS levels were also evaluated under H2O2 treatments. At the whole organism scale, both H2O2 concentrations didn’t affect the survival and animal tissues exhibited a high resistance to H2O2 treatments. Moreover, no bleaching has been observed, even at high H2O2 concentration and after long exposure (7 days). Although, the community has suggested the role of ROS as the cause of bleaching, our results indicating the absence of bleaching under high H2O2 concentration may exculpate this specific ROS from being involved in the molecular processes inducing bleaching. However, counterintuitively, the symbiont compartment appeared sensitive to an H2O2 burst as it displayed oxidative protein damages, despite an enhancement of antioxidant capacity. The in vitro assays allowed highlighting an intrinsic high capacity of isolated animal cells to deal with pro-oxidative conditions, although we observed differences on tolerance between H2O2 treatments. The 200 μM H2O2 concentration appeared to correspond to the tolerance threshold of animal cells. Indeed, no disequilibrium on redox state was observed and only a cell growth decrease was measured. Contrarily, the 500 μM H2O2 concentration induced a stress state, characterized by a cell viability decrease from 1 day and a drastic cell growth arrest after 7 days leading to an uncomplete recovery after treatment. In conclusion, this study highlights the overall high capacity of cnidarian cells to cope with H2O2 and opens new perspective to investigate the molecular mechanisms involved in this peculiar resistance.